Preoperative treatment of locally advanced gastrointenstinal cancer - Ljiljana Vasić (Биомедицинска истраживања, 2019)
Surgical treatment of locally advanced gastrointestinal cancer alone does not exhibit satisfactory local disease control and survival rate. The advantage of using radio and chemotherapy at this stage is to reduce the likelihood of developing local recurrence with an extension of survival time, while the disadvantages are the increase in postoperative mortality and morbidity. The subject of many studies has been to determine the localization in which preoperative treatment is justified, as well as the order for applying radio and chemotherapy, without endangering the patient's life. This paper summarizes the current findings on the investigated problem suggesting that preoperative treatment has influenced the change in surgical indications for the treatment of cancer in this region. The use of preoperative treatment in esophagus, stomach, rectum and anus cancer is justified since it reduces the likelihood of developing local recurrence. Nevertheless, it does not increase the survival rate where patients with the rectal and stomach cancer are concerned. Furthermore, preoperative treatment increases the postoperative mortality and morbidity of esophagus and anus cancer, while its use in the treatment of pancreatic cancer is still the subject of many clinical studies. In surgery, preoperative treatment has led to modification in the techniques used in the treatment of rectal cancer, as well as to the reconsideration of the extent of lymphadenectomy of the esophagus and stomach cancer, while in the case of anus cancers, surgical treatment is not considered to be the initial form of curative therapy at this stage.
Keywords: preoperative treatment; locally advanced stage; gastrointestinal tract; radiotherapy; chemotherapy; recurrence; survival rate